2011
DOI: 10.1042/bj20101909
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small molecules that elevate Klotho expression

Abstract: The absence of Klotho (KL) from mice causes the development of disorders associated with human aging and decreased longevity, whereas increased expression prolongs lifespan. With age, KL protein levels decrease, and keeping levels consistent may promote healthier aging and be disease-modifying. Using the KL promoter to drive expression of luciferase, we conducted a high-throughput screen to identify compounds that activate KL transcription. Hits were identified as compounds that elevated luciferase expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 49 publications
(70 reference statements)
3
33
0
1
Order By: Relevance
“…Our study revealed that the function of NMDARs, which is critical for normal cognition and impaired by A␤ and tau (Nakazawa et al, 2004;Lee and Silva, 2009;Hoover et al, 2010;Ittner et al, 2010;Cissé et al, 2011;Li et al, 2011), represents a potential convergence point at which klotho may counteract the adverse effects of these pathogens. Klotho elevation prevented the depletion of NMDAR subunits GluN1, GluN2A, and GluN2B and ameliorated impairments of NMDAR-dependent synaptic plasticity in the hippocampus of hAPP mice.…”
Section: Klotho Modulates the Distribution And Function Of Nmdarsmentioning
confidence: 62%
See 2 more Smart Citations
“…Our study revealed that the function of NMDARs, which is critical for normal cognition and impaired by A␤ and tau (Nakazawa et al, 2004;Lee and Silva, 2009;Hoover et al, 2010;Ittner et al, 2010;Cissé et al, 2011;Li et al, 2011), represents a potential convergence point at which klotho may counteract the adverse effects of these pathogens. Klotho elevation prevented the depletion of NMDAR subunits GluN1, GluN2A, and GluN2B and ameliorated impairments of NMDAR-dependent synaptic plasticity in the hippocampus of hAPP mice.…”
Section: Klotho Modulates the Distribution And Function Of Nmdarsmentioning
confidence: 62%
“…Hippocampus was dissected, homogenized, and sonicated in ice-cold lysis buffer [1ϫ PBS, pH 7.4, 1 mM DTT, 0.5 mM EDTA, 0.5% Triton, 0.1 M PMSF, protease inhibitor mixture (Roche), and phosphatase inhibitors 2 and 3 (Sigma-Aldrich)]. Following the addition of guanidine (final concentration 5 M), samples were rehomogenized and analyzed for levels of human A␤ 1-x and A␤ 1-42 by ELISA as described previously (Johnson-Wood et al, 1997;.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, our results reveal that Klotho exerts its neuroprotective effect via the Trx/Prx antioxidative system, which is important for regulating the redox balance in the brain. Finally, our studies suggest that Klotho-enhancing compounds may provide future therapeutic approaches for neurodegenerative disorders (90,91).…”
Section: Discussionmentioning
confidence: 77%
“…Tümör baskılayıcı genlerin DNMT enzimleri ile epigenetik olarak anlatım düzeylerinin düşürülmesi ya da inaktivasyonu kanser gelişiminde önemli bir etken olarak karşımıza çık-maktadır (72). Çeşitli kanser türleri ile ilişkilendirilen ve eksikliğinde yaşlanmaya benzer belirtilerin ortaya çıkmasına neden olan Kl proteininin sentezinin regüle edilmesi bir kısım hastalıkların tedavisine olanak sağlayabilir (73)(74)(75).…”
Section: Klotho Geni Ve Metilasyonunclassified